Eukaryotic Cell Toxicity and HSA Binding of [Ru(Me4phen)(bb7)]2+ and the Effect of Encapsulation in Cucurbit[10]uril - Sun, Biyun; Musgrave, Ian F.; Day, Anthony I.; Heimann, Kirsten; Keene, F. Richard; Collins, J. Grant (Frontiers in Chemistry, 2018)
The toxicity (IC50) of a series of mononuclear ruthenium complexes containing bis[4(4'-methyl-2,2'-bipyridyl)]-1,n-alkane (bbn) as a tetradentate ligand against three eukaryotic cell lines − BHK (baby hamster kidney), Caco-2 (heterogeneous human epithelial colorectal adenocarcinoma) and Hep-G2 (liver carcinoma) − have been determined. The results demonstrate that cis-α-[Ru(Me4phen)(bb7)]2+ (designated as α-Me4phen-bb7, where Me4phen = 3,4,7,8-tetramethyl-1,10-phenanthroline) showed little toxicity towards the three cell lines, and was considerably less toxic than cis-α-[Ru(phen)(bb12)]2+ (α-phen-bb12) and the dinuclear complex [{Ru(phen)2}2{μ-bb12}]4+. Fluorescence spectroscopy was used to study the binding of the ruthenium complexes with human serum albumin (HSA). The binding of α-Me4phen-bb7 to the macrocyclic host molecule cucurbit[10]uril (Q[10]) was examined by NMR spectroscopy. Large upfield 1H NMR chemical shift changes observed for the methylene protons in the bb7 ligand upon addition of Q[10], coupled with the observation of several intermolecular ROEs in ROESY spectra, indicated that α-Me4phen-bb7 bound Q[10] with the bb7 methylene carbons within the cavity and the metal center positioned outside one of the portals. An α-Me4phen-bb7 -Q[10] binding constant of 9.9 ± 0.2 x 106 M-1 was determined by luminescence spectroscopy. Q[10]-encapsulation decreased the toxicity of α-Me4phen-bb7 against the three eukaryotic cell lines and increased the binding affinity of the ruthenium complex for HSA. Preliminary confocal microscopy experiments indicated that the level of accumulation of α-Me4phen-7 in BHK cells is unlikely to be significantly affected by Q[10]-encapsulation. Taken together, the combined results suggest that α-Me4phen-7 could be a good candidate as a new antimicrobial agent, and Q[10]-encapsulation could be a method to improve the pharmacokinetics of the ruthenium complex.